Inside the Olympic industry : power, politics, and activism - Lenskyj, Helen (SUNY series on sport, culture, and social relations., 2000)
"In a expose of the Olympic industry, Helen Jefferson Lenskyj goes beyond the media hype of international goodwill and spirited competition to uncover a darker side of the global Games. She reports on the pre- and post-Olympic impacts from recent host cities, bribery investigations and their outcomes, grassroots resistance movements, and the role of the mass media in the controversy. An accessible book about a complex subject that touches the hearts of sports fans everywhere, Inside the Olympic Industry is a behind-the-scenes look at the politics surrounding the choice of Sydney, Australia as host city for the 2000 Summer Olympic Games."--Jacket